A negative or positive signal? The impact of food recalls on negative word-of-mouth (N-WOM). (June 2021) - Seo, Soobin; Jang, SooCheong (Shawn)
Abstract: Considering the increasing number of food recall incidents in the restaurant industry, it is crucial to examine the impact of food recall on consumers' negative word-of-mouth (N-WOM) intentions. This study examined the effects of the food recall announcement on consumers' N-WOM intentions, focusing specifically on crisis level and two brand-related forms of leverage, brand equity and branding strategy. A 2 (crisis level: low/high) x 2 (brand equity: low/high) x 2 (branding strategy: corporate branding/house of brands) scenario-based research design was employed using a self-administered online survey. The food recall announcement was found to be effective in reducing N-WOM intentions only for loyal consumers when the crisis level was high. Further, the use of the corporate branding strategy was effective in reducing N-WOM intentions compared to the house-of- branding strategy. These findings provide useful guidelines to practitioners on how to effectively announce food recalls.